Estudo da associação da atividade sexual com as disfunções do assoalho pélvico e suas implicações na qualidade de vida em mulheres - Macedo, Sandra Reboucas [UNIFESP] (2018)
Postmenopausal age and status are factors that negatively affect sexual activity. being married facilitates sexual activity in women, with dap. the presence of genital prolapse and urinary incontinence do not alter sexual activity. nsa women with genital prolapse present an important impairment of their quality of life when compared to sas...